FISHERMAN WIFE CONTRIBUTION TO HOUSEHOLD INCOME IN BAGAN BARAT VILLAGE BANGKO DISTRICT ROKAN HILIR REGENCY RIAU PROVINCE - Irvan Pratama Helmira; Firman Nugroho; Eni Yulinda (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT            His research was conducted in May 2018 in Bagan Barat Village, Bangko District, Rokan Hilir Regency, Riau Province. The research objectives were to find out the activities of fishermen's wives, describe the use of time, and find out the contribution of fishermen's wives in helping to improve the economy of fishermen households to reduce family burden in Bagan Barat Village, Bangko District, Rokan Hilir Regency. carried out in census, that is fisherman households have wives who work. The number of respondents is 48 people.The results of this study indicate that the activities of the wives of fishermen including Undomestik activities are selling cakes as many as 3 people (6.25%), selling juice as much as 4 people (8.33%), stall for nine basic necessities (16.67%), processing salted fish as many as 10 people (20.83%), processing shrimp paste as many as 9 people (18.75%), and selling fried foods as many as 3 people (6.25%), while the activities of fishermen's wives included in public activities namely, civil servants civilians as many as 2 people (4.17%), honorary employees as many as 2 people (4.17%), fish sellers as many as 4 people (8.33%), selling rujak as much as 2 people (4.17%), and bang employees liau as many as 1 person (2.08%). The average outpouring of work time on undomestic activities is 57.95 hours / week, while the average outpouring of work time in public activities is 41.36 hours / week. The average income contribution of fisherman wives in Bagan Barat Village is 36.91%.                                      Keywords: Contributions, Undomestic and Public Activities, Outpouring of Working Time